lead-acid batteries
Patent Information
- Application Number
- JP2025058842
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166100000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to lead-acid batteries. BACKGROUND ART
[0002] Patent Document 1 proposes "a lead-acid battery comprising: a positive electrode plate having a current collector and a positive electrode material supported by the current collector; and a negative electrode plate, wherein the total pore volume per unit mass of the positive electrode material is 0.167 cm 3 / g or less, the positive electrode material contains fibers, and the average specific surface area of the fibers measured by the BET method using krypton gas as the adsorption gas is 0.25 m 2 / g or more".
[0003] Patent Document 2 proposes "a separator for a lead-acid battery, which comprises a crystalline region and an amorphous region, and has a degree of crystallinity represented by 100×Ic / (Ic+Ia) of 20% or more in the X-ray diffraction spectrum of the separator". Ic is the integrated intensity of the diffraction peak having the maximum peak height among the diffraction peaks corresponding to the crystalline region, and Ia is the integrated intensity of the halo corresponding to the amorphous region. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0004] PATENT DOCUMENT 1 Japanese Unexamined Patent Publication No. 2019-67741 PATENT DOCUMENT 2 Japanese Unexamined Patent Publication No. 2022-186309 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0005] In recent years, with the advent of vehicles controlled by idling stop-start (ISS) and OTA (Over The Air) technology, the load borne by lead-acid batteries has been increasing more and more. When charge-discharge cycles with a large discharge depth (hereinafter also referred to as "deep discharge cycles") are repeated, softening and falling off of the positive electrode material of the lead-acid battery are prone to occur, so it is necessary to improve the durability of the positive electrode material.
[0006] In order to improve the durability of the positive electrode material, it has been proposed to add fibers to the positive electrode material (Patent Document 1).
[0007] On the other hand, polyolefin microporous separators are prone to oxidative degradation. Due to oxidation, the oxidized portion is decomposed and the pore size increases. As a result, the fallen-off positive electrode material easily penetrates into the inside of the separator, and short circuits caused by the fallen-off positive electrode material are likely to occur. Consequently, it becomes difficult to improve the life performance of the lead-acid battery. [Means for Solving the Problems]
[0008] One aspect of the present disclosure includes a positive electrode plate, a negative electrode plate, a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolytic solution, wherein the positive electrode plate includes a positive electrode material, the negative electrode plate includes a negative electrode material, the separator includes a crystalline region and an amorphous region, and in the X-ray diffraction spectrum of the separator, a ratio R represented by A1 / (A1+A2) is 0.20 or more, A1 is the integrated intensity of the peak attributed to the (110) plane of the crystalline region, A2 is the integrated intensity of the halo peak attributed to the amorphous region, the positive electrode material includes fibers, and the surface area of the fibers per 1 g of the positive electrode material is 1.35 cm 2 or more, relating to a lead-acid battery. [Effects of the Invention]
[0009] According to the present disclosure, the deep discharge cycle life performance of the lead-acid battery is improved. [Brief Description of the Drawings]
[0010] [Figure 1] This is a partially cutaway perspective view showing the external appearance and internal structure of a lead-acid battery according to one embodiment of the present invention. [Modes for carrying out the invention]
[0011] The embodiments of this disclosure will be described below with examples, but this disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be given as examples, but other numerical values and materials may be applied as long as the effects of this disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "greater than or equal to numerical value A and less than or equal to numerical value B". In the following description, when lower and upper limits of numerical values relating to specific physical properties or conditions are given as examples, either of the given lower limits and either of the given upper limits can be arbitrarily combined, as long as the lower limit is not greater than or equal to the upper limit. When multiple materials are given as examples, one of them may be selected and used alone, or two or more may be used in combination.
[0012] Furthermore, this disclosure encompasses any combination of matters described in two or more claims, which may be arbitrarily selected from the multiple claims set forth in the attached claims. In other words, any combination of matters described in two or more claims, which may be arbitrarily selected from the multiple claims set forth in the attached claims, is possible, provided that no technical inconsistency arises.
[0013] (1) The lead-acid battery according to this embodiment (hereinafter also referred to as "lead-acid battery (B)") comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode material. The negative electrode plate includes a negative electrode material. The separator includes a crystalline region and an amorphous region, and the ratio R (hereinafter sometimes referred to as crystallinity R), expressed as A1 / (A1+A2) in the X-ray diffraction spectrum of the separator, is 0.20 or greater. Here, A1 is the integrated intensity of the peak attributed to the (110) plane of the crystalline region. A2 is the integrated intensity of the halo peak attributed to the amorphous region. The positive electrode material includes fibers, and the surface area of the fibers per gram of the positive electrode material is 1.35 cm².2 That's all.
[0014] Separators whose crystallinity R satisfies the above range (hereinafter also referred to as "separator (SS)") have a large proportion of crystalline regions, resulting in regularly arranged molecules and high oxidation resistance. As a result, even if detached electrode material penetrates into the separator, the detached electrode material acts as an oxidizing agent, suppressing oxidation of the separator. Consequently, the rate of oxidative degradation of the separator (SS) is slow, resulting in a longer lifespan.
[0015] In addition, the surface area of the fibers contained in the positive electrode material is set at 1.35 cm² per gram of positive electrode material. 2 By implementing the above, the detachment of the positive electrode material due to softening is suppressed, and consequently, oxidative degradation caused by the detached positive electrode material penetrating into the separator is also suppressed. As a result, by combining it with a separator (SS), an even longer lifespan can be achieved.
[0016] In the lead-acid battery (B) described in (1) above, the fibers adhere closely to the positive electrode material, maintain high adhesion between the positive electrode material particles, and suppress detachment due to softening of the positive electrode material particles. Therefore, even when a separator (SS) is used, high adhesion between the positive electrode material particles that have become coarser due to charging and discharging can be maintained, and detachment can be suppressed via van der Waals forces between the fibers and the positive electrode material particles.
[0017] In the charged state, the positive electrode material forms a network of bonded lead dioxide particles. When the discharge reaction changes the lead dioxide to lead sulfate, its volume expands by approximately 1.5 times. Repeated deep discharge cycles typically cause the bonds between lead compound particles in the positive electrode material to break, isolating some of the lead compounds. As a result, softening progresses from the surface of the positive electrode plate, leading to the detachment of the positive electrode material. To suppress such softening and detachment, it is considered necessary that the contact area between the fibers contained in the positive electrode material and the positive electrode material itself be sufficiently large.
[0018] While fibers retain active material by intertwining with each other and suppress the shedding of positive electrode material particles, conventional fibers with a small contact area with the positive electrode material cannot suppress the shedding of electrode material in areas that are not in contact. As a result, the shedding electrode material easily accelerates oxidative degradation of the separator, and the shedding positive electrode material easily penetrates into the separator.
[0019] In contrast, by setting the surface area of the fibers contained in the positive electrode material to the above range relative to the mass of the positive electrode material, the contact area of the fibers with the positive electrode material becomes sufficiently large, reducing the amount of electrode material that is not in contact, and making it easier to hold the positive electrode material particles through entanglement between the fibers. Furthermore, there are many areas where the fibers are entangled, making it easier to hold larger positive electrode material particles.
[0020] However, while fibers are effective in suppressing the shedding of softened positive electrode material particles, particularly large ones, they may not be able to suppress the shedding of relatively small softened positive electrode material particles. Small softened positive electrode material particles tend to penetrate into the pores of the separator.
[0021] A separator (SS) is used, but the surface area of the fibers contained in the positive electrode material is outside the above range (1.35 cm²). 2 If the amount is less than 1 / g, the shedding of the positive electrode material, which is the cause of oxidative degradation of the separator, cannot be suppressed, and both large-particle and small-particle active material can penetrate into the separator (SS). As a result, although the high oxidation resistance of the separator (SS) slows down the rate of oxidative degradation of the separator (SS) and extends its lifespan, a large accumulation of active material within the separator may occur, and a sufficiently long lifespan may not be achieved.
[0022] On the other hand, the surface area of the fibers contained in the positive electrode material is within the above range (1.35 cm²). 2 / g or more), shedding of the positive electrode material is suppressed, but shedding of the positive electrode material with a small particle size is difficult to suppress. At this time, if the separator (SS) is not used, the shed active material with a small particle size may penetrate into the separator, and the oxidative deterioration of the separator progresses due to the shed active material with a small particle size, making it difficult to achieve a long service life.
[0023] In contrast, when the surface area of the fibers contained in the positive electrode material falls within the above range, shedding of the positive electrode material is suppressed. Although shedding of the positive electrode material with a small particle size is difficult to suppress and the shed electrode material with a small particle size may penetrate into the separator, the use of the separator (SS) can suppress the oxidative deterioration of the separator (SS) due to its high oxidation resistance. As a result, compared with the case where the separator (SS) is used and the surface area of the fibers is outside the above range, and the case where the separator (SS) is not used and the surface area of the fibers falls within the above range, a significantly longer service life can be achieved when the separator (SS) is used and the surface area of the fibers falls within the above range.
[0024] The crystallinity R is 0.20 or more, and from the viewpoint of ensuring higher life performance, it may be 0.23 or more or 0.25 or more. The crystallinity R may be 0.40 or less, and may be 0.35 or less or 0.30 or less.
[0025] The surface area of the fibers is 1.35 cm per 1 g of the positive electrode material 2 or more, and from the viewpoint of ensuring higher life performance, it may be 1.67 cm per 1 g of the positive electrode material 2 or more. On the other hand, in order to increase the surface area of the fibers, the conductivity of the positive electrode material decreases (the resistance increases) as the content ratio of the fibers in the positive electrode material increases and / or the specific surface area of the fibers increases. The surface area of the fibers is 5.00 cm per 1 g of the positive electrode material 2 or less, and may be 4.50 cm per 1 g of the positive electrode material 2 or less, or 4.00 cm 2 or less.
[0026] (2) In the lead-acid battery (B) described in (1) above, the average fiber diameter of the fibers is preferably 10 μm or less.
[0027] The thinner the fiber diameter, the larger the contact area between the lead compound constituting the positive electrode material and the fiber, and the greater the effect of suppressing softening and detachment of the positive electrode material due to the fiber. Therefore, by making the average fiber diameter of the fiber in the lead-acid battery (B) described in (1) above 10 μm or less, the fiber has a large specific surface area, which increases the contact area between the lead compound constituting the positive electrode material and the fiber. In addition, even with the same fiber content, the number of fibers increases, resulting in a structure in which many thin fibers are interwoven within the positive electrode material. As a result, the adhesion between the fiber and the positive electrode material is further improved, the binding between the positive electrode material particles is maintained at a higher level, and the effect of suppressing detachment due to softening of the positive electrode material particles is greatly enhanced.
[0028] In the lead-acid battery (B) described in (1) above, the average fiber diameter of the fibers may be 9 μm or less. From the viewpoint of ensuring sufficient strength of the fibers themselves, the average fiber diameter of the fibers is preferably 0.1 μm or more, and may also be 0.5 μm or more. The average fiber diameter of the fibers can be controlled during the fiber synthesis process.
[0029] (3) In the lead-acid battery (B) described in (1) or (2) above, the average fiber diameter of the fibers is preferably 1 μm to 8 μm.
[0030] In the lead-acid battery (B) described in (1) or (2) above, if the average fiber diameter of the fibers is in the range of 1 μm to 8 μm, the fibers have a larger specific surface area, thus increasing the contact area between the lead compound constituting the positive electrode material and the fibers. Furthermore, by making the average fiber diameter of the fibers 1 μm or more, higher strength of the fibers can be ensured. This improves the adhesion between the fibers and the positive electrode material, further increasing the effect of suppressing the shedding of the positive electrode material. From the viewpoint that the effect of suppressing the shedding of the positive electrode material is further increased by ensuring that the fibers have a larger specific surface area and higher strength of the fibers, the average fiber diameter of the fibers may be 2 μm to 8 μm, 1 μm to 7 μm, 2 μm to 7 μm, 3 μm to 8 μm, or 4 μm to 8 μm.
[0031] (4) In the lead-acid battery (B) described in any one of (1) to (3) above, it is preferable that the surface of the fiber has irregularities. Furthermore, it is preferable that the irregularities on the surface of the fiber are formed along the circumferential direction of the fiber. The circumferential direction of the fiber is any direction that intersects the longitudinal direction of the fiber. Such a direction is, for example, a direction that has an angle of 45° or more on average with the longitudinal direction of the fiber.
[0032] In the lead-acid battery (B) described in (4) above, the friction between the lead compound particles and the fibers is increased by the surface irregularities of the fibers. In particular, when the surface irregularities of the fibers are formed along the circumferential direction of the fibers, the friction is greater when the lead compound particles try to move in the longitudinal direction of the fibers. Therefore, an effect is obtained in which the expansion of the positive electrode material along the longitudinal direction of the fibers is suppressed.
[0033] In the lead-acid battery (B) described in (4) above, the surface irregularities of the fibers may be formed in a ripple-like pattern along the circumferential direction of the fibers. The trajectory of the ripple-like irregularities extending on the surface of the fibers is long, and the shape of the irregularities is complex. Therefore, such irregularities are likely to engage with particles of the lead compound that are trying to move in the longitudinal direction of the fibers. Thus, the effect of suppressing the expansion of the positive electrode material along the longitudinal direction of the fibers is further enhanced.
[0034] The irregularities may be formed on the fibers beforehand, or they may be formed on smooth fibers by a predetermined method, or they may be formed during the manufacturing process of the lead-acid battery. One method for forming irregularities on the surface of fibers is chemical treatment, which modifies the fiber surface using chemicals such as acids and alkalis. Other methods for forming irregularities on the surface of fibers include plasma treatment, which modifies the fiber surface using plasma, corona treatment, which modifies the fiber surface using high-voltage discharge, and UV irradiation treatment, which modifies the fiber surface using ultraviolet light. Yet another method is sandblasting, for example. Sandblasting is a process in which fine powder harder than the fiber is impacted onto the fiber.
[0035] When using methods such as plasma treatment, corona treatment, or UV irradiation to create irregularities on fibers, the state of the irregularities may be altered by changing the output value of the processing device, the processing time, or both. In sandblasting, the speed of the fine powder impacting the fibers and the processing time can also be changed.
[0036] (5) In the lead-acid battery (B) described in any one of (1) to (4) above, the separator preferably has a thickness of 0.10 mm or more and 0.30 mm or less. From the viewpoint of obtaining a longer lifespan, the thickness of the separator is preferably 0.10 mm or more, and more preferably 0.15 mm or more. On the other hand, from the viewpoint of keeping the resistance of the separator low, the thickness of the separator is preferably 0.30 mm or less, and more preferably 0.25 mm or less or 0.20 mm or less. The thickness of the separator means the average thickness of the part of the separator facing the electrode material. If the separator comprises a base portion and ribs erected from at least one surface of the base portion, the thickness of the separator is the average thickness of the base portion. If an adhesive member (mat, pasting paper, etc.) is attached to the separator, the thickness of the adhesive member is not included in the thickness of the separator.
[0037] (6) In the lead-acid battery (B) described in any one of (1) to (5) above, the surface area of the fibers per gram of positive electrode material is 3.00 cm². 2 The above is preferable. From the viewpoint of further suppressing the shedding of positive electrode material particles due to softening, the surface area of the fibers per gram of positive electrode material should be 3.00 cm². 2 It is more preferable that the length be greater than or equal to 3.50 cm. 2 Above, or 4.00 cm 2 Over 4.50cm 2 That's fine too.
[0038] The lead-acid battery (B) relating to this disclosure may be a valve-regulated lead-acid battery (VRLA type battery) or a liquid-type battery (vented type battery).
[0039] A lead-acid battery (B) comprises a positive electrode plate, a negative electrode plate, a separator interposed between the positive and negative electrode plates, and an electrolyte. The electrolyte contains sulfuric acid. Charging and discharging proceed through the movement of sulfate ions between the positive and negative electrode plates and the electrolyte.
[0040] A positive electrode plate, a negative electrode plate, and a separator constitute an electrode group. The electrode group, together with the electrolyte, constitutes a cell. One electrode group constitutes one cell. A lead-acid battery (B) comprises one or more cells by comprising one or more electrode groups. There is no particular limit to the number of positive and negative electrode plates included in one electrode group. An electrode group comprising a lead-acid battery (B) according to this disclosure may include, for example, a total of 12 or more positive and negative electrode plates. Multiple electrode groups are usually housed in separate cell chambers and connected in series with one another.
[0041] The negative electrode plate includes a negative electrode current collector and a negative electrode material. The negative electrode material is a negative electrode active material that exhibits capacity through an oxidation-reduction reaction, and contains at least lead during charging and at least lead sulfate during discharging.
[0042] The positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode material is a positive electrode active material that exhibits capacity through oxidation-reduction reactions, and contains at least lead dioxide during charging and at least lead sulfate during discharge.
[0043] In this specification, the fully charged state of a liquid lead-acid battery is defined according to the definition in JIS D5301:2019. More specifically, in a water bath at 25°C ± 2°C, the 20-hour rate current I is charged until the terminal voltage (in volts) or the electrolyte density converted to 20°C shows a constant value with three significant figures for three consecutive 15-minute intervals. 20 Twice the current 2I 20 (Unit: A) The fully charged state of a lead-acid battery is defined as the state in which it has been charged. Note that the 20-hour rate current I 20 This refers to a current (A) that is 1 / 20th of the Ah value listed in the rated capacity. The value listed as the rated capacity is a value in Ah (ampere-hour). The unit of the current set based on the value listed as the rated capacity is A (ampere).
[0044] Furthermore, in the case of a valve-regulated lead-acid battery, a fully charged state is defined as a 20-hour rate current of 1 in an air chamber at 25°C ± 2°C. 20 5 times the current 5I 20 The battery was then charged at a constant current and voltage of 2.67V / cell (16.00V for a lead-acid battery with a nominal voltage of 12V), and the charging process was terminated when the total charging time reached 24 hours.
[0045] A fully charged lead-acid battery is a lead-acid battery that has been charged to its full capacity after chemical formation. The timing for charging a lead-acid battery to its full capacity can be immediately after chemical formation, or after a certain amount of time has passed since formation (e.g., 720 hours or less). For example, a lead-acid battery that has been chemically formed and is in use (preferably in the early stages of use) may be charged.
[0046] In this specification, a battery in its initial use refers to a battery that has not been used for very long and has not deteriorated much (for example, a battery that has been in use for less than 720 hours, including the time elapsed since chemical preparation).
[0047] The lead-acid battery (B) according to an embodiment of the present invention will be described in more detail below with reference to the drawings. However, the present invention is not limited to the following embodiments.
[0048] The following describes examples of components of a lead-acid battery (B).
[0049] Figure 1 shows the external appearance and part of the internal structure of a lead-acid battery 1 according to one embodiment. The lead-acid battery 1 comprises a battery case 12 that houses an electrode plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by a partition wall 13. Each cell chamber 14 houses one electrode plate group 11. The opening of the battery case 12 is closed with a lid 15 equipped with a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When replenishing water, the vent plug 18 is removed and the water is supplied. The vent plug 18 may also have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0050] Each electrode plate group 11 is constructed by stacking multiple negative electrode plates 2 and positive electrode plates 3 via separators 4. The separators 4 are separators (SS) whose pore size distribution satisfies the above relationship. Here, a bag-shaped separator 4 that houses the negative electrode plates 2 is shown, but the form of the separator other than the pore size distribution is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, a negative electrode shelf 6 connecting multiple negative electrode plates 2 in parallel is connected to a through-connector 8, and a positive electrode shelf 5 connecting multiple positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 on the outside of the lid 15. In the cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf 6, and a through-connector 8 is connected to the positive electrode shelf 5. The negative electrode column 9 is connected to a negative electrode terminal 16 on the outside of the lid 15. Each through-connector 8 passes through a through-hole provided in the partition wall 13, connecting the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0051] Note that Figure 1 is merely an example of a liquid-type lead-acid battery, and the structure of the lead-acid battery (B) according to this disclosure is not limited to the example shown in the figure. Furthermore, the following description does not limit the configuration of the lead-acid battery (B) according to the present invention.
[0052] (Negative electrode plate) The negative electrode plate of a lead-acid battery (B) consists of a negative electrode current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. In some cases, an adhesive member may be attached to the negative electrode plate. In this case, the adhesive member is included in the negative electrode plate. When the negative electrode plate includes an adhesive member, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the adhesive member.
[0053] The negative electrode current collector included in the negative electrode plate may be formed by casting lead (Pb) or lead alloy (NA), or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the negative electrode current collector is preferable because it makes it easier to support the negative electrode material.
[0054] The lead alloy used for the negative electrode current collector may be any of the following: lead alloy (NA), Pb-Sb alloy, Pb-Ca alloy, or Pb-Ca-Sn alloy. The lead alloy (NA) may also be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The negative electrode current collector may have lead alloy layers of different compositions, and the alloy layer may be a single layer or multiple layers.
[0055] The negative electrode material contained in the negative electrode plate contains Pb. Pb is a negative electrode active material that exhibits capacity through oxidation-reduction reactions and is included in the negative electrode material as lead or lead sulfate.
[0056] The negative electrode material may further contain organic shrinkage inhibitors, carbonaceous materials, barium sulfate, reinforcing materials, and the like.
[0057] Examples of organic shrinkage inhibitors include lignin, lignin sulfonic acid, and synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenolic compounds). The content of the organic shrinkage inhibitor in the negative electrode material is, for example, 0.01% by mass or more. The content of the organic shrinkage inhibitor is, for example, 1.2% by mass or less.
[0058] Examples of carbonaceous materials include carbon black, graphite, hard carbon, and soft carbon. The carbonaceous material content in the negative electrode material is, for example, 0.1% by mass or more. The carbonaceous material content may also be, for example, 3.5% by mass or less.
[0059] The barium sulfate content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.
[0060] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). The reinforcing material content in the negative electrode material is, for example, 0.03% by mass or more. Alternatively, the reinforcing material content in the negative electrode material is, for example, 0.6% by mass or less.
[0061] The negative electrode plate can be formed by filling a negative electrode current collector with negative electrode paste, aging and drying it to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is made by kneading lead powder, an organic shrinkage inhibitor, barium sulfate, etc., with water and sulfuric acid. The negative electrode active material in the charged state is spongy lead, but the unformed negative electrode plate is usually made using lead powder. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at high humidity.
[0062] The chemical conversion can be carried out by immersing the electrode plate group, including the unconverted negative electrode plate, in the sulfuric acid-containing electrolyte in the lead-acid battery (B) case and then charging the electrode plate group. However, the chemical conversion may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group. Spongy lead is produced by the chemical conversion.
[0063] (Positive plate) For example, a paste-type positive electrode plate is used as the positive electrode plate. A paste-type positive electrode plate comprises a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector. In addition, materials such as mats and pasting paper may be attached to the positive electrode plate. Since such attached materials are used integrally with the positive electrode plate, they are included in the positive electrode plate. When the positive electrode plate includes attached materials, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector and attached materials.
[0064] The positive electrode current collector included in the positive electrode plate may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the positive electrode current collector is preferable because it makes it easier to support the positive electrode material.
[0065] The lead alloy used for the positive electrode current collector may be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The positive electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be a single layer or multiple layers.
[0066] The positive electrode material contained in the positive electrode plate includes a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through oxidation-reduction reactions, and contains fibers as an additive. The positive electrode material may also contain other additives as needed.
[0067] The fiber content in the positive electrode material may be, for example, 0.005% by mass or more and 0.25% by mass or less, 0.01% by mass or more and 0.23% by mass or less, 0.02% by mass or more and 0.23% by mass or less, 0.02% by mass or more and 0.2% by mass or less, 0.07% by mass or more and 0.2% by mass or less, or 0.14% by mass or more and 0.2% by mass or less.
[0068] The BET specific surface area of the fibers in the positive electrode material is 0.3 m². 2 / g or more 1.0m 2 It may be less than / g. Such fibers have a very large specific surface area, and a very large contact area between the fibers and the lead compound. The large contact area allows the fibers and lead compound to intertwine, increasing the bonding force between the lead compounds, which suppresses softening and detachment of the positive electrode material and enables a long lifespan. From the viewpoint of ease of manufacturing the positive electrode plate, the BET specific surface area is 1.0 m². 2 / g or less, 0.6m 2 / g or less or 0.5m 2 It may be less than / g. The BET specific surface area is determined using the BET formula by a gas adsorption method with krypton gas as the adsorbing gas.
[0069] The effect of suppressing softening and shedding by fibers can also depend on the material of the fibers. Preferably, the fibers are made of a resin that is thin yet strong and stable in the presence of sulfuric acid.
[0070] As the fibers, inorganic fibers or organic fibers may be used, or both inorganic and organic fibers may be used. From the viewpoint of easily controlling the BET specific surface area, organic fibers are preferred. Examples of resins (or polymers) that constitute the organic fibers include acrylic resins, polyolefin resins (polypropylene resins, polyethylene resins, etc.), polyester resins (including polyalkylene arylates (polyethylene terephthalate, etc.)), and celluloses (cellulose, cellulose derivatives (cellulose ethers, cellulose esters, etc.)). Rayon is also included in the celluloses.
[0071] The resin constituting the fiber may be at least one selected from the group consisting of polyester and polyolefin, as it has excellent acid or alkali resistance. Examples of polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Examples of polyolefins include polyethylene, polypropylene (PP), and ethylene-propylene copolymer. Among these, PET has excellent acid resistance and mechanical strength. Therefore, fibers made of PET have a fine average fiber diameter and can secure a large surface area even in small quantities, making it easy to improve the deep discharge life of lead-acid batteries (B). Furthermore, PET fibers are inexpensive.
[0072] For example, 85% or more of the fiber may be composed of polyester. Fibers containing such a high percentage of polyester are usually called polyester fibers (e.g., PET fibers). Also, 85% or more of the fiber may be composed of polyolefin. Fibers containing such a high percentage of polyolefin are usually called polyolefin fibers (e.g., polyethylene fibers, polypropylene fibers). Similarly, fibers in which 85% or more of the fiber is composed of acrylic resin are called acrylic fibers.
[0073] The fibers may contain one type of resin, or two or more types. Furthermore, the positive electrode material may contain multiple fibers formed from different resins. Among these resins, using an acrylic resin makes it easier to form fine wrinkles on the fiber surface, thus making it easier to control the BET specific surface area within a desired range.
[0074] The surface area S of the fiber is 1.35 cm² per gram of positive electrode material. 2 That concludes the explanation. The surface area of fibers per gram of positive electrode material is calculated as the surface area of the fibers contained in 1 gram of positive electrode material. Specifically, if X grams of positive electrode material contains Y grams of fibers, and the surface area of the Y grams of fibers is Z cm², then the surface area of the fibers is Z cm². 2 In this case, the surface area of the fibers per gram of positive electrode material is Z / X (cm²). 2The surface area of a single fiber is calculated as πDL / g. Assuming the fiber shape is cylindrical with length L, and the average fiber diameter is D, the surface area of one fiber is calculated as πDL. If the positive electrode material Wg contains N fibers, the surface area of the fibers per gram of positive electrode material is calculated as NπDL / W. Furthermore, the volume of a cylinder with a surface area of NπDL is π(D / 2). 2 Since it is NL, the fiber density d (g / cm³) 3 In the case of ), if the mass w and average fiber diameter D of the positive electrode material W (g) are known, then w / d = π(D / 2) 2 From the NL relationship, NL(=w / (d·π(D / 2)) 2 )) can be determined, and NπDL / W can be calculated.
[0075] Here, the fiber density d (g / cm³) 3 ) is the standard fiber density described in books or technical documents, and can also be measured by preparing a resin sample and following the "Method for Measuring Density and Specific Gravity of Non-Foamed Plastics" specified in JIS K 7112:1999. For example, the "Textile Handbook, 3rd Edition," edited by the Textile Institute of Japan and published by Maruzen Publishing Co., Ltd. (2004), lists the specific gravity of fibers. The numerical value of the specific gravity of fibers coincides with the numerical value of the fiber density d. If there is a range in the fiber density or specific gravity described in books or technical documents, the average value of the described numerical range may be used as the fiber density d. For example, the "Textile Handbook, 3rd Edition" states that the specific gravity of acrylic fibers is 1.14 to 1.17. In that case, the fiber density d of acrylic fibers (g / cm³) 3 ) is 1.155 ≈ 1.16 (g / cm³) 3 ) can be considered as such.
[0076] The method for manufacturing the fibers contained in the positive electrode material is not particularly limited. The fibers may be formed, for example, by wet spinning. In wet spinning, fibers can be formed by spinning a solution (spinning base solution) in which a resin is dissolved in a solvent into a liquid coagulation solution. At this time, the diffusivity of the solvent from the coagulated product of the spinning base solution, which has solidified in the coagulation solution, can be adjusted by selecting the solvent used in the spinning base solution and the composition of the coagulation solution. This adjusts the degree of volume reduction in the coagulation product, making it easier to form fine wrinkles on the surface of the fibers. In this way, the BET specific surface area of the fibers can be adjusted.
[0077] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described in JIS L 1030-1:2024. The fibers may be recovered by pulling them out of the positive electrode material with tweezers, or they may be recovered from the residue after dissolving the lead compound contained in the positive electrode material, as described below.
[0078] The positive electrode material is recovered from the positive electrode plate by the following procedure. First, a fully charged lead-acid battery is disassembled, and the obtained positive electrode plate is washed with water for 3 to 4 hours to remove the electrolyte from the positive electrode plate. The washed positive electrode plate is dried in a constant temperature bath at 60°C ± 5°C for 5 hours or more. After drying, if the positive electrode plate contains adhesive material, the adhesive material is removed from the positive electrode plate by peeling. The fibers contained in the adhesive material are not included in the fibers of the present invention. If adhesive material was attached to the positive electrode plate, the surface of the positive electrode plate is scraped to a depth of 0.03 mm to 0.20 mm until the residue of the adhesive material is removed. Then, a sample of the positive electrode material for analysis is obtained by taking a sample of the positive electrode material from near the center when the positive electrode plate is viewed from the front, without crushing it.
[0079] The fibers are recovered from the positive electrode material sample by the following procedure. First, a predetermined amount Wg (e.g., about 70g) of positive electrode material sample is crushed and accurately weighed. At this time, the positive electrode material contained in one or more positive electrode plates may be used as the sample.
[0080] Next, the pulverized sample is added to a mixed solution of acetic acid-sodium acetate solution and sodium thiosulfate solution (acetic acid concentration 1.7 mol / L, sodium acetate concentration 6.1 mol / L, sodium thiosulfate concentration 0.5 mol / L), and the soluble components are dissolved while stirring at room temperature. Then, the resulting residue is filtered using a membrane filter (average pore size: 0.45 μm or less) while washing with deionized water. This allows the fibers contained in the positive electrode material to be obtained as solid matter on the filter paper.
[0081] A fiber sample for analysis is obtained by washing and drying the resulting solid. The mass w of the fiber sample is measured. The percentage of the mass w of the fiber sample relative to the mass W of the positive electrode material sample is the fiber content in the positive electrode material.
[0082] The resin constituting the fibers can be identified by analyzing the infrared absorption spectrum of the fiber sample. Method B (film method) specified in JIS L 1030-1:2024 may be used as the analytical method.
[0083] Specifically, the fiber sample is dissolved in an appropriate dissolving reagent (see Table A), poured into an evaporating dish, and dried under vacuum or by heating to a temperature that does not decompose the sample. Next, the dried film is peeled off without tearing, cut to an appropriate size, and the infrared absorption spectrum is measured in accordance with JIS K 0117:2017. The film should be of a thickness that makes it transparent. Also, the size of the film will vary depending on the infrared spectrophotometer used, so it should be at least 1 cm. 2 That concludes this section.
[0084] Table A exemplifies the main absorption bands and characteristic wavenumbers of the infrared absorption spectra of various fibers, as well as the dissolving reagents. The absorption bands and characteristic wavenumbers of each fiber vary by ±20 cm depending on the infrared spectrophotometer used. -1 There are differences in degree.
[0085] [Table A]
[0086] The average fiber diameter D of a fiber is determined by selecting any 20 fibers from a fiber sample, measuring the fiber diameter (the dimension perpendicular to the length of the fiber) at any point on each fiber, and taking the arithmetic mean of the measurements. The average fiber diameter D of a fiber may also be measured using a scanning electron microscope (SEM) image of the fiber.
[0087] The average fiber diameter D of the fibers may be in the range of 0.1 μm to 16 μm, 0.5 μm to 12 μm, 1 μm to 10 μm, 1 μm to 8 μm (or 2 μm to 8 μm), 1 μm to 7 μm (or 2 μm to 7 μm), or 3 μm to 8 μm (or 4 μm to 8 μm).
[0088] By identifying the resin that makes up the fibers, the fiber density d (g / cm³) can be determined. 3 The following is determined: fiber density d, mass w of fibers contained in the positive electrode material Wg, average fiber diameter D, and w / d = π(D / 2) 2 The NL relationship allows us to calculate the surface area of the fibers per gram of positive electrode material (NπDL / W).
[0089] Unformed paste-type positive electrode plates are obtained by filling a positive electrode current collector with positive electrode paste, followed by maturation and drying. The positive electrode paste is prepared by kneading lead powder, and optionally additives (such as reinforcing materials), with water and sulfuric acid.
[0090] A positive electrode plate can be obtained by chemically treating an untreated positive electrode plate. Chemical treatment can be carried out by immersing the electrode plate group, including the untreated positive electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery (B), and then charging the electrode plate group. However, chemical treatment may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group.
[0091] (Separator) As the separator (SS) placed between the negative electrode and the positive electrode, at least one selected from, for example, nonwoven fabric and microporous membrane can be used. The material of the separator (SS) is not particularly limited as long as it has a pore size distribution and ratio r1 within the above range.
[0092] Nonwoven fabrics are mats composed of interwoven fibers rather than woven fibers, and are primarily fiber-based. For example, 60% or more of the nonwoven fabric is made up of fibers. Suitable fibers include glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (such as polyethylene terephthalate fibers), etc.), and pulp fibers. Glass fibers are preferred among these. Nonwoven fabrics may also contain other components besides fibers, such as acid-resistant inorganic powders and polymers as binders.
[0093] A microporous membrane is a porous sheet mainly composed of non-fibrous components. For example, it can be obtained by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. Microporous membranes are preferably composed of acid-resistant materials, and preferably mainly composed of polymer components. Polyolefins (such as polyethylene and polypropylene) are preferred as polymer components. Examples of pore-forming agents include polymer powders and oils.
[0094] The separator may consist solely of a nonwoven fabric, or solely of a microporous membrane. The separator may also be a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same type of material bonded together, or a laminate of different or the same type of material with interlocking protrusions and indentations.
[0095] The separator may be in the form of a sheet or a bag. A single sheet-shaped separator may be placed between the positive and negative electrodes. The electrode plates may be sandwiched between folded sheet-shaped separators. The positive electrode sandwiched between folded sheet-shaped separators and the negative electrode sandwiched between folded sheet-shaped separators may be stacked on top of each other, or one of the positive and negative electrodes may be sandwiched between folded sheet-shaped separators and stacked on top of the other electrode plate. When a bag-shaped separator is used, the bag-shaped separator may contain either the positive electrode or the negative electrode.
[0096] The separator may or may not have ribs. A separator with ribs, for example, comprises a base portion and ribs erected from the surface of the base portion. The ribs may be provided on only one surface of the separator or each base portion, or on both surfaces. The base portion of the separator refers to the part of the separator's components excluding protrusions such as ribs, and is a sheet-like portion that defines the outer shape of the separator.
[0097] The thickness of the separator may be 0.09 mm or more and 0.30 mm or less (or 0.25 mm or less), 0.09 mm or more and 0.20 mm or less, 0.10 mm or more (or 0.15 mm or more) and 0.30 mm or less, 0.10 mm or more (or 0.15 mm or more) and 0.25 mm or less, or 0.10 mm or more (or 0.15 mm or more) and 0.20 mm or less.
[0098] In the pore size distribution of the separator (SS), the cumulative pore volume V1 for pore sizes from 0.005 μm to 10 μm is 0.8 cm³. 3 / g or more 2.0cm 3 The ratio of the pore volume V2 with a pore diameter of 0.1 μm to 10 μm to the total pore volume V1 may be 50% or more (r1 = V2 / V1). Such a separator has many pores in the range of 0.1 μm to 10 μm, which allows for high diffusion of the electrolyte and keeps the resistance of the separator low.
[0099] The pore size distribution of the separator (SS) is determined by the mercury intrusion method. The ratio r1 is the ratio of the total volume of pores with a pore size of 0.1 μm to 10 μm to the total volume of pores with a pore size of 0.05 μm to 10 μm in the pore size distribution determined by the mercury intrusion method.
[0100] The ratio r1 may be 50% or more, or 60% or more. For example, the ratio r1 may be 70% or less. The ratio r1 may be 50% or more and 70% or less, or 50% or more and 60% or less.
[0101] The cumulative pore volume V1 is 0.8 cm³. 3 / g or more 2.0cm 3 / g or less, 1.0cm 3 / g or more 2.0cm 3 / g or less, 0.8cm 3 / g or more 1.2cm 3 Less than / g, or 1.0cm 3 / g or more 1.2cm 3 It may be less than / g.
[0102] The separator (SS) may be, for example, a microporous membrane separator containing a polymer material (hereinafter also referred to as the base polymer). The base polymer may contain polyolefins. A polyolefin is a polymer containing at least olefin units (i.e., a polymer containing at least monomer units derived from olefins). Polyolefins and other base polymers may be used in combination as the base polymer. The ratio of polyolefins to the total base polymer contained in the separator is, for example, 50% by mass or more, may be 80% by mass or more, or may be 90% by mass or more. The ratio of polyolefins is, for example, 100% by mass or less. The base polymer may consist only of polyolefins.
[0103] Polyolefins include, for example, homopolymers of olefins, copolymers containing different olefin units, and copolymers containing olefin units and copolymerizable monomer units. Copolymers containing olefin units and copolymerizable monomer units may contain one or more types of olefin units. Copolymers containing olefin units and copolymerizable monomer units may also contain one or more types of copolymerizable monomer units. Copolymerizable monomer units are monomer units derived from polymerizable monomers other than olefins that are copolymerizable with olefins.
[0104] Examples of polyolefins include, for example, at least C 2-3 Examples include polymers containing olefins as monomer units. 2-3 Examples of olefins include at least one selected from the group consisting of ethylene and propylene. Examples of polyolefins include polyethylene, polypropylene, and C 2-3 Copolymers containing olefins as monomer units (e.g., ethylene-propylene copolymers) are more preferred. Among polyolefins, it is preferable to use polyolefins containing at least ethylene units (e.g., polyethylene, ethylene-propylene copolymers). Polyolefins containing ethylene units (e.g., polyethylene, ethylene-propylene copolymers) may be used in combination with other polyolefins.
[0105] Microporous film separators containing the above polymer material include crystalline regions where the base polymer molecules are relatively regularly arranged (i.e., highly aligned) and amorphous regions with low alignment. Therefore, in the XRD spectrum of the separator, diffraction peaks from the crystalline regions are observed, as well as scattered light from the amorphous regions, which is observed as a halo.
[0106] In the X-ray diffraction spectrum of the separator, the integrated intensity of the diffraction peak corresponding to the (110) plane among the diffraction peaks corresponding to the crystalline region is defined as A1, and the integrated intensity of the halo peak attributed to the amorphous region is defined as A2. The ratio R expressed as A1 / (A1+A2) is defined as the degree of crystallinity R. The degree of crystallinity R is 0.20 or higher. In this case, the degradation of the separator due to oxidation of the base polymer is suppressed, and high lifetime performance is obtained.
[0107] The degree of crystallinity may be 0.20 or higher, and from the viewpoint of ensuring higher lifetime performance, it may be 0.23 or higher or 0.25 or higher. The degree of crystallinity may be 0.40 or lower, and may be 0.35 or lower or 0.30 or lower. When the degree of crystallinity is within this range, it is easier to ensure the flexibility of the separator and easier to manufacture.
[0108] The degree of crystallinity may be 0.20 or higher (or 0.23 or higher) and 0.40 or lower, 0.20 or higher (or 0.23 or higher) and 0.35 or lower, 0.20 or higher (or 0.23 or higher) and 0.30 or lower, 0.25 or higher and 0.40 or lower (or 0.35 or lower), or 0.25 or higher and 0.30 or lower.
[0109] For example, in the XRD spectrum of a separator containing polyolefins with ethylene units, diffraction peaks corresponding to the (110) plane of the crystalline region are observed in the range where 2θ is between 20° and 22.5°, and diffraction peaks corresponding to the (200) plane of the crystalline region are observed in the range where 2θ is between 23° and 24.5°. In addition, a halo in the amorphous region is observed in the range where 2θ is between 17° and 27°.
[0110] The integrated intensities of diffraction peaks and halos are obtained by fitting the diffraction peaks from the crystalline region and the halos from the amorphous region to the XRD spectrum of the separator. The degree of crystallinity is then determined using the obtained integrated intensities A1 of the diffraction peak corresponding to the (110) plane and A2 of the halo.
[0111] A separator can be obtained, for example, by extruding a resin composition containing a base polymer, a pore-forming agent, and a penetrating agent (surfactant) into a sheet, stretching it, and then removing at least a portion of the pore-forming agent. Removing at least a portion of the pore-forming agent creates micropores in the matrix of the base polymer. The separator (or the resin composition used to produce the separator) may contain inorganic particles. After the removal of the pore-forming agent, the sheet-shaped separator is dried as needed. For example, the degree of crystallinity can be adjusted by adjusting at least one selected from the group consisting of the cooling rate of the sheet during extrusion, the stretching ratio during stretching, and the temperature during drying. For example, rapidly cooling the sheet during extrusion, increasing the stretching ratio, or lowering the temperature during drying tends to increase the degree of crystallinity. Stretching may be performed by biaxial stretching, but is usually performed by uniaxial stretching. The sheet-shaped separator may be folded into an accordion shape or processed into a bag shape as needed.
[0112] The pore structure and ratio r1 within the separator can be adjusted by adjusting the affinity between the base polymer and the pore-forming agent and / or penetrant, adjusting the dispersibility of the pore-forming agent, selecting the type and / or particle size of the inorganic particles, selecting the type of penetrant, adjusting the amount of inorganic particles, the amount of the pore-forming agent, and / or the amount of the penetrant, and / or adjusting the amount of functional groups and / or atoms present on the surface of the inorganic particles.
[0113] For separator analysis or size measurement, unused separators or separators removed from fully charged lead-acid batteries in their early stages of use are used. Separators removed from lead-acid batteries are washed and dried prior to analysis or measurement.
[0114] The separators removed from lead-acid batteries are cleaned and dried using the following procedure: The separators are immersed in pure water for 1 hour to remove sulfuric acid from them. Then, the separators are removed from the liquid and allowed to stand at 25°C ± 5°C for at least 16 hours to dry.
[0115] The XRD spectrum of the separator is measured by irradiating the separator surface with X-rays perpendicular to it. The sample for measurement is prepared by processing the portion of the separator facing the electrode material into a strip shape. For separators with ribs, the base portion is processed into a strip shape to avoid including the ribs. XRD spectrum measurement and fitting are performed under the following conditions. (Measurement conditions) Measurement device: RINT-TTR2, manufactured by Rigaku Corporation. Fitting: FT (Step Scan) method Measurement angle range: 15-35° Step width: 0.02° Measurement speed: 5° / min XRD data processing: XRD pattern analysis software (PDXL2, manufactured by Rigaku) was used.
[0116] The cumulative pore volume V1 and ratio r1 of the separator can be determined by using a mercury porosimeter to determine the pore distribution of a sample processed into a strip shape under the following conditions. Mercury porosimeter: Autopore IV9510, manufactured by Shimadzu Corporation. Measurement pressure range: 4 psia (≒27.6 kPa) to 60,000 psia (≒414 MPa) Pore size distribution: 0.01 μm to 50 μm
[0117] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled if necessary.
[0118] The electrolyte may further contain at least one metal ion selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0119] The specific gravity of the electrolyte at 20°C is, for example, 1.10 or higher. The specific gravity of the electrolyte at 20°C may also be 1.35 or lower. These specific gravity values are for the electrolyte of a fully charged lead-acid battery (B).
[0120] The matters described herein can be combined in any way.
[0121] [Examples] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to the following examples. Here, a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah was assembled. The 5-hour rate capacity is the capacity when discharged at a current (A) of 1 / 5 of the Ah value stated in the rated capacity.
[0122] [Evaluation Method] (1) Light load life test The battery life will be evaluated in accordance with JIS D5301:2019. Here, a fully charged lead-acid battery with a rated voltage of 12V will be repeatedly discharged and charged under the following conditions, and the number of cycles until it reaches the end of its life will be evaluated. Here, the discharge time for the light load life test will be set to 240 seconds to simulate a deep discharge cycle test.
[0123] In the light-load life test, regardless of the difference in the 20-hour rate capacity of the test battery, the procedure is carried out according to (a) to (e) below. Here, the 20-hour rate capacity is the capacity when discharged to the discharge termination voltage at a current (A) of 1 / 20 of the Ah value stated in the rated capacity. The steps (a) to (e) below are carried out in the gas phase at 40℃±2℃.
[0124] (a) Discharge: Discharge at a current of 25A for 240 seconds. (b) Charging: Charge at a constant voltage of 14.8V for 600 seconds (however, the maximum current is 100A). (c) Repeat: Repeat steps (a) and (b) above 480 times, with each step counting as one cycle. (d) Take a break for 40 to 60 hours. (e) Test discharge: After (d) above, discharge for 30 seconds at the rated cold cranking current Icc specified in JIS D5301:2019. The point at which the voltage drops to 7.2V 30 seconds after the start of discharge is considered the end of the life cycle, and the number of cycles until the end of the life cycle is defined as the life cycle count.
[0125] Since discharge with the rated cold cranking current Icc is performed every 480 cycles, the number of cycles at which the voltage at 30 seconds is 7.2V can be determined by linear interpolation from a graph with the voltage at 30 seconds in the Icc discharge on the vertical axis and the number of cycles on the horizontal axis, and this can be used as the life cycle count.
[0126] Examples 1-20, Comparative Examples 1-10 (Batteries E1~E20, batteries C1~C10) Each lead-acid battery was manufactured using the following procedure. (1) Fabrication of separators A resin composition containing 100 parts by mass of polyethylene (PE), approximately 160 parts by mass of silica particles, approximately 80 parts by mass of paraffinic oil as a pore-forming agent, and 2 parts by mass of a penetrating agent was extruded into a sheet, stretched, and then a portion of the pore-forming agent was removed to produce a microporous membrane with ribs on one side. At this time, the degree of crystallinity R of the separator, which is determined by the procedure described above, was set to the value shown in Table 1 for the positive electrode plate taken from a fully charged lead-acid battery (B). The degree of crystallinity R was adjusted by controlling at least one of the following: the cooling rate of the sheet during extrusion molding, the stretching ratio during the stretching process, and the temperature during the drying process.
[0127] Next, a sheet-like microporous membrane was folded in half so that ribs were arranged on the outer surface to form a bag, and the overlapping ends were pressed together to obtain a bag-shaped separator.
[0128] (2) Fabrication of the positive electrode plate A positive electrode paste was prepared by mixing lead oxide, fibers, water, and sulfuric acid. The positive electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed positive electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.6 mm.
[0129] The average fiber diameter of the fibers used in the positive electrode paste, as determined by the procedure described above, was as shown in Table 1 for a positive electrode plate taken from a fully charged lead-acid battery (B). The resin constituting the fibers was PET (polyethylene terephthalate). The fibers were adjusted so that the surface area of the fibers per gram of positive electrode material, as determined by the procedure described above, was as shown in Table 1 for a positive electrode plate taken from a fully charged lead-acid battery (B).
[0130] (3) Fabrication of the negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate, lignin, water, and sulfuric acid. The negative electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, which served as the negative electrode current collector. By aging and drying, an unformed negative electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.3 mm was obtained. The amounts of carbon black, barium sulfate, and lignin used were adjusted so that the content of each component in the negative electrode plate taken from a fully charged lead-acid battery (B) was 0.3 mass%, 2.1 mass%, and 0.1 mass%, respectively.
[0131] (4) Fabrication of lead-acid battery (B) The untreated negative electrode plates were placed in the bag-shaped separator prepared in (1), stacked with the positive electrode plates, and an electrode plate group was formed with 7 untreated negative electrode plates and 6 untreated positive electrode plates.
[0132] The tabs of the positive electrode plates and the tabs of the negative electrode plates were welded to the positive and negative electrode trays, respectively, using the cast-on-strap (COS) method. The six electrode plates were inserted into a polypropylene battery case, connected in series, and electrolyte was poured in. A chemical conversion was then performed inside the battery case to assemble a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah.
[0133] A sulfuric acid solution was used as the electrolyte. The specific gravity of the electrolyte after chemical conversion was 1.285 at 20°C.
[0134] (5) Evaluation The obtained lead-acid battery (B) was subjected to a light-load life test and evaluated according to the procedure described above. The evaluation results are shown in Table 1. In Table 1, the evaluation results of the light-load life test are shown as relative values with battery C1 of Comparative Example 1 set to 100.
[0135] [Table 1]
[0136] Examples 21-25 (Batteries E21~E25) (1) The resin constituting the fibers was changed as shown in Table 2. The degree of crystallinity R of the separator was set to the value shown in Table 2. The lead-acid battery (B) was assembled and evaluated in the same manner as in Example 1.
[0137] Table 2 shows the evaluation results. In Table 2, in the fiber column, PU means polyurethane, PE means polyethylene, and PP means polypropylene.
[0138] [Table 2]
[0139] Table 1 shows that the degree of crystallinity R of the separator is 0.2 or higher, and the surface area of the fibers contained in the positive electrode material is 1.35 cm² per gram of positive electrode material. 2 In the lead-acid battery (B) described above, a remarkably long lifespan was achieved.
[0140] From batteries C1 to C5, there is a tendency for longer lifespan to be observed as the surface area of the fibers contained in the positive electrode material increases. From batteries C6 to C10, there is a tendency for longer lifespan to be observed as the crystallinity R of the separator increases. However, from a comparison between batteries C1 and C2, the surface area of the fibers is 1.08 cm² per gram of positive electrode material.2 From 1.35cm 2 The improvement in lifespan due to this increase is at most about 2%. Similarly, comparing batteries C1 and C6, the improvement in lifespan due to increasing the crystallinity R of the separator from 0.15 to 0.20 is at most about 2%.
[0141] In contrast, in battery E1, the surface area of the fibers is 1.35 cm² per gram of positive electrode material. 2 By increasing the value and raising the degree of crystallinity R of the separator to 0.20, a 15% improvement in battery life was observed compared to battery C1, resulting in a significant improvement in lifespan performance.
[0142] A comparison of batteries E1 to E20 shows that the degree of crystallinity R of the separator is in the range of 0.2 to 0.4, and the surface area of the fibers contained in the positive electrode material is 1.35 cm² per gram of positive electrode material. 2 More than 3.0cm 2 We were able to confirm that significantly higher lifespan performance can be obtained within the following range. [Industrial applicability]
[0143] The lead-acid battery according to this disclosure is suitable, for example, as a lead-acid battery for vehicles employing a start-stop system, and can also be suitably used as a power source for industrial energy storage devices such as electric vehicles (forklifts, etc.). These applications are merely examples. The applications of the lead-acid battery according to the present invention are not limited to these. [Explanation of Symbols]
[0144] 1: Lead-acid battery, 2: Negative electrode plate, 3: Positive electrode plate, 4: Separator, 5: Positive electrode shelf, 6: Negative electrode shelf, 7: Positive electrode column, 8: Through connector, 9: Negative electrode column, 11: Electrode plate group, 12: Battery case, 13: Partition wall, 14: Cell chamber, 15: Cover, 16: Negative electrode terminal, 17: Positive electrode terminal, 18: Electrode cap
Claims
1. The device comprises a positive electrode plate, a negative electrode plate, a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolyte. The positive electrode plate includes a positive electrode material, The aforementioned negative electrode plate includes a negative electrode material, The separator includes a crystalline region and an amorphous region. In the X-ray diffraction spectrum of the separator, the ratio R represented by A1 / (A1+A2) is 0.20 or greater. A1 is the integrated intensity of the peak attributed to the (110) plane of the crystalline region, A2 is the integrated intensity of the halo peak attributed to the amorphous region. The positive electrode material includes fibers, The surface area of the fibers per gram of the positive electrode material is 1.35 cm². 2 That concludes the explanation of lead-acid batteries.
2. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 10 μm or less.
3. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 1 μm to 8 μm.
4. The surface of the aforementioned fiber has irregularities, The lead-acid battery according to any one of claims 1 to 3, wherein the irregularities are formed along the circumferential direction of the fibers.
5. The lead-acid battery according to claim 1, wherein the separator has a thickness of 0.10 mm or more and 0.30 mm or less.
6. The surface area of the fibers per gram of the positive electrode material is 3.00 cm². 2 The lead-acid battery according to claim 1.
Citation Information
Patent Citations
Lead storage battery
JP2019067741A
Separator for lead storage battery and lead storage battery including the same
JP2022186309A